2017
DOI: 10.1016/j.cortex.2017.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional apathy and executive dysfunction in amyotrophic lateral sclerosis

Abstract: Apathy and cognitive dysfunction are prominent symptoms of Amyotrophic lateral sclerosis (ALS). More specifically ALS patients show increased Initiation apathy-a lack of motivation for self-generation of thoughts as assessed by the Dimensional Apathy Scale. This study aimed to investigate the cognitive underpinnings of apathy subtypes in ALS. We hypothesized that increased Initiation apathy would be associated deficits on tests of intrinsic response generation, such as verbal fluency. We also explored the rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 54 publications
3
33
0
1
Order By: Relevance
“… 5 , 29 Neuropsychological studies have shown that letter fluency impairment may represent a difficulty in cognitive initiation, 4 , 35 which in turn is related to the high frequency of apathy in ALS. 36 Similar to executive functioning and letter fluency, apathy has been associated with reduced fractional anisotropy in the right anterior cingulate cortex 37 and the dorsolateral and orbitomedial prefrontal cortex. 38 Pathologic TAR DNA-binding protein 43 inclusions have been suggested to spread predictably in ALS, 39 beginning in the primary motor cortex, spinal cord, and cranial nerves and spreading to the reticular formation of the brainstem, prefrontal cortex, and finally hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“… 5 , 29 Neuropsychological studies have shown that letter fluency impairment may represent a difficulty in cognitive initiation, 4 , 35 which in turn is related to the high frequency of apathy in ALS. 36 Similar to executive functioning and letter fluency, apathy has been associated with reduced fractional anisotropy in the right anterior cingulate cortex 37 and the dorsolateral and orbitomedial prefrontal cortex. 38 Pathologic TAR DNA-binding protein 43 inclusions have been suggested to spread predictably in ALS, 39 beginning in the primary motor cortex, spinal cord, and cranial nerves and spreading to the reticular formation of the brainstem, prefrontal cortex, and finally hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…Apathy or demotivation is the most common behavioural impairment in ALS 36 37. Although some symptoms of depression and apathy may overlap, a dissociation in ALS has been demonstrated,37 and the distinct profile of initiation apathy found in ALS has been related to a cognitive failure to initiate as demonstrated by verbal fluency deficits 38. Early signs of apathy may have been captured as premorbid mood disorders on the CARE-MND platform.…”
Section: Discussionmentioning
confidence: 99%
“…Probably, the higher prevalence of negative/inhibited behaviours with respect to positive/disinhibited ones makes aberration of sexual activities less present and described. In fact, apathy is the most frequently reported symptom occurring in around 50% of patients,43 with consequent reductions in sexual interest and activities that could be less recorded and investigated, even if with a relevant impact on the patient–carer relationship. Maybe the issue of apathy-related diminished sexual interest and activities should be investigated as distinct from emotional-driven inhibition as described above, with the possible development of different interventions when appropriate.…”
Section: Discussionmentioning
confidence: 99%